2009
DOI: 10.4049/jimmunol.0901071
|View full text |Cite
|
Sign up to set email alerts
|

Genetically Detoxified Pertussis Toxin Induces Th1/Th17 Immune Response through MAPKs and IL-10-Dependent Mechanisms

Abstract: Genetically detoxified pertussis toxin (dPT) maintains the protein structure and the immunological properties, but not the enzymatic activity. In search of an adjuvant able to direct polarization of T cells to induce/potentiate protective immune response to a variety of infectious disease, we investigated the role played by dPT on human dendritic cell-driven Th polarization and analyzed the intracellular signaling events. To reach these aims, we used a highly purified dPT preparation devoid of contamination an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
59
0
4

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 56 publications
(67 citation statements)
references
References 55 publications
4
59
0
4
Order By: Relevance
“…Indeed, the release of IL-12 was also shown to be upregulated in IL-32g-stimulated DCs. The simultaneous stimulation of Th1 and Th17 type responses has also been described previously by other investigators (35)(36)(37). Both the Th1 and Th17 subsets promote cellular immune function and can induce inflammation and autoimmune diseases, such as inflammatory bowel diseases and collagen-induced arthritis (17, 20, 38, 39).…”
Section: Discussionsupporting
confidence: 57%
“…Indeed, the release of IL-12 was also shown to be upregulated in IL-32g-stimulated DCs. The simultaneous stimulation of Th1 and Th17 type responses has also been described previously by other investigators (35)(36)(37). Both the Th1 and Th17 subsets promote cellular immune function and can induce inflammation and autoimmune diseases, such as inflammatory bowel diseases and collagen-induced arthritis (17, 20, 38, 39).…”
Section: Discussionsupporting
confidence: 57%
“…We have recently shown that MDDCs stimulated with genetically detoxified PT induced a mixed Th1/ Th17 response (15), and in another study PT-deficient B. pertussis was described as a poor inducer of both IFN-g and IL-17 in mice (17). The findings presented here demonstrate that detoxification of PT in BPZE1 results in two interesting properties: it abrogates toxicity and the inhibitory effects on chemotaxis while the immunomodulatory properties are retained.…”
Section: Discussionsupporting
confidence: 54%
“…In particular, our studies shed light on the contribution of several virulence factors, such as adenylate cyclase toxin (9-11), lipooligosaccharide (12,13), and PT (14,15).…”
mentioning
confidence: 96%
“…Although many cell surface sialoglycoproteins may serve as PTX receptors, specific receptors for PTX have not been identified [13]. PTX induces intracellular signals in part through TLR4, and JNK, p38, ERK1/2, and NF-κB are all activated in response to PTX, similar to the response to LPS [6,14]. LPS signals through TLR4 via two major pathway types: the MyD88-dependent activation of NF-κB, which results in the induction of inflammatory genes, such as TNF, IL-6, and IL-1β, and TRIF-dependent pathways, which involve the induction of type I IFNs and secondary response genes that are activated by IFN-β in an autocrine/paracrine manner [15,16].…”
Section: Introductionmentioning
confidence: 99%